Solid pseudopapillary neoplasm of the pancreas: a retrospective study of 195 cases - Fu, Chang; Li, Xiaocong; Wang, Yongxin; Wang, Chuangshi; Jin, Hengwei; Liu, Kai; Xu, Hongji (Frontiers in Oncology, 2024)
Objective Solid pseudopapillary neoplasm of the pancreas (SPN) is a rare exocrine tumor of the pancreas. The aim of our study is to summarize the clinical features of SPN and to analyze the risk factors for malignant SPN. Methods From May 2013 to September 2022, patients who were pathologically confirmed to have SPN were retrospectively reviewed. Demographic data, clinical and pathological features, follow-up data were collected and analyzed. To investigate the factors influencing the benign or malignant nature of SPN, we employed logistic regression. Additionally, we utilized Kaplan-Meier curves to depict and analyze the overall prognosis. Results A total of 195 patients were included, 163 of whom were female and the average age of all patients was 31.7 years old. Among 195 patients, 101 patients (51.8%) had no obvious clinical symptoms and their pancreatic lesions were detected during routine examination. The primary symptom was abdominal pain and distension in 64 cases (32.8%). The maximum diameter of SPN tumors ranged from 1-17 cm (mean 6.19 cm). Forty-eight postoperative complications developed in 43 (22.1%) patients. After a median follow-up duration of 44.5 months, the overall 5-year survival rate was 98.8% and the recurrence rate was 1.5%. Furthermore, we observed a statistically significant difference in the completeness of the tumor capsule between benign and malignant SPN. Conclusion SPN is associated with a favorable long-term survival after surgery in our large sample size cohort. For malignant SPN, tumor capsule incompleteness is an independent risk factor.